Genomewide Meta‐Analysis Validates a Role for S1PR1 in Microtubule Targeting Agent‐Induced Sensory Peripheral Neuropathy. Issue 3 (2nd August 2020) - Chua, Katherina C.; Xiong, Chenling; Ho, Carol; Mushiroda, Taisei; Jiang, Chen; Mulkey, Flora; Lai, Dongbing; Schneider, Bryan P.; Rashkin, Sara R.; Witte, John S.; Friedman, Paula N.; Ratain, Mark J.; et al.
Abstract : Microtubule targeting agents (MTAs) are anticancer therapies commonly prescribed for breast cancer and other solid tumors. Sensory peripheral neuropathy (PN) is the major dose‐limiting toxicity for MTAs and can limit clinical efficacy. The current pharmacogenomic study aimed to identify genetic variations that explain patient susceptibility and drive mechanisms underlying development of MTA‐induced PN. A meta‐analysis of genomewide association studies (GWAS) from two clinical cohorts treated with MTAs (Cancer and Leukemia Group B (CALGB) 40502 and CALGB 40101) was conducted using a Cox regression model with cumulative dose to first instance of grade 2 or higher PN. Summary statistics from a GWAS of European subjects ( n  = 469) in CALGB 40502 that estimated cause‐specific risk of PN were meta‐analyzed with those from a previously published GWAS of European ancestry ( n  = 855) from CALGB 40101 that estimated the risk of PN. Novel single nucleotide polymorphisms in an enhancer region downstream of sphingosine‐1‐phosphate receptor 1 ( S1PR1 encoding S1PR1 ; e.g., rs74497159, βCALGB 40101 per allele log hazard ratio (95% confidence interval (CI)) = 0.591 (0.254–0.928), βCALGB 40502 per allele log hazard ratio (95% CI) = 0.693 (0.334–1.053); PMETA  = 3.62 × 10 −7 ) were the most highly ranked associations based on P values with risk of developing grade 2 and higher PN. In silico functional analysis identified multiple regulatory elements and potential enhancer activity for S1PR1 within this genomic region. Inhibition of S1PR1 function in induced pluripotent stem cell‐derived human sensory neurons shows partial protection against paclitaxel‐induced neurite damage. These pharmacogenetic findings further support ongoing clinical evaluations to target S1PR1 as a therapeutic strategy for prevention and/or treatment of MTA‐induced neuropathy.